Astroglial and microglial pathology in Down syndrome: Focus on Alzheimer's disease - García, Octavio; Flores-Aguilar, Lisi (Frontiers in Cellular Neuroscience, 2022)
Down syndrome (DS) arises from the triplication of human chromosome 21 and is considered the most common genetic cause of intellectual disability. Glial cells, specifically astroglia and microglia, display pathological alterations that might contribute to DS neuropathological alterations. Further, in middle adulthood, people with DS develop clinical symptoms associated with premature aging and Alzheimer’s disease (AD). Overexpression of the amyloid precursor protein (APP) gene, encoded on chromosome 21, leads to increased amyloid-β (Aβ) levels and subsequent formation of Aβ plaques in the brains of individuals with DS. Aβ deposition might contribute to astroglial and microglial reactivity, leading to neurotoxic effects and elevated secretion of inflammatory mediators. This review discusses evidence of astroglial and microglial alterations that might be associated with the AD continuum in DS.